The Pediatric Rheumatology International Trials Organization American-College-of-Rheumatology provisional criteria for the evaluation of response to therapy in juvenile systemic lupus erythematosus: Prospective validation of the definition of improvement - Ruperto, N.; Ravelli, A.; Oliveira, S.; Alessio, M.; Mihaylova, D.; Pasic, S.; Cortis, E.; Apaz, M.; Burgos-Vargas, R.; Kanakoudi-Tsakalidou, F.; Norambuena, X; Corona, F.; et al. (Wiley-Blackwell, 2006)
Objective. To use the Pediatric Rheumatology International Trials Organization (PRINTO) core set of outcome measures to develop a validated definition of improvement for the evaluation of response to therapy in juvenile systemic lupus erythematosus (SLE).Methods. Thirty-seven experienced pediatric rheumatologists from 27 countries, each of whom had specific experience in the assessment of juvenile SLE patients, achieved consensus on 128 patient profiles as being clinically improved or not improved. Using the physicians' consensus ratings as the gold standard measure, the chi-square, sensitivity, specificity, false-positive and false-negative rates, area under the receiver operating characteristic curve, and kappa level of agreement for 597 candidate definitions of improvement were calculated. Only definitions with a kappa value greater than 0.7 were retained. The top definitions were selected based on the product of the content validity score multiplied by its kappa statistic.Results. The definition of improvement with the highest final score was at least 50% improvement from baseline in any 2 of the 5 core set measures, with no more than 1 of the remaining worsening by more than 30%.Conclusion. PRINTO proposes a valid and reproducible definition of improvement that reflects well the consensus rating of experienced clinicians and that incorporates clinically meaningful change in core set measures in a composite end point for the evaluation of global response to therapy in patients with juvenile SLE. The definition is now proposed for use in juvenile SLE clinical trials and may help physicians to decide whether a child with SLE responded adequately to therapy.
Keywords: juvenile systemic lupus erythematosus; core set; response to therapy; disease activity; consensus